Flagellate Erythema Secondary to Bleomycin for Non-Seminomatous Testis Tumor - de Lacerda Pereira, Felipe; Alexandre Protzner Morbeck, Igor (Brazilian Journal of Case Reports, 2021)
The development of flagellate erythema secondary to bleomycin treatment is a rare adverse effect. The prevalence varies between 8 to 22% of patients and it is becoming rarer. Flagellate erythema presents as a scaly erythematous papule. A lower amount of bleomycin hydrolase in regions with reduced production, such as skin and lungs, decreases bleomycin degradation, which allows its accumulation in tissues, triggering an inflammatory process, especially in patients with lower basal enzyme function. We report a clinical case of a severe presentation of flagellate erythema secondary to a patient ongoing bleomycin, etoposide and platinum (BEP) based chemotherapy of non-seminomatous testis cancer.